2016
DOI: 10.1016/j.foodchem.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brewing conditions on the antioxidant capacity of twenty-four commercial green tea varieties

Abstract: A novel paper-based Nanoceria Reducing Antioxidant Capacity (NanoCerac) assay for antioxidant detection (Sharpe, Frasco, Andreescu, & Andreescu, 2012), has been adapted for the first time as a high-throughput method, in order to measure the effect of brewing conditions and re-infusion on the antioxidant capacity of twenty-four commercial green teas. The oxygen radical absorbance capacity (ORAC) assay, frequently applied to complex foods and beverages, was used as a comparator measure of antioxidant capacity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 32 publications
4
31
0
2
Order By: Relevance
“…Figure 3A shows that the total antioxidant capacity of A. borneensis leaves increases abruptly with brewing temperature (in the range of 10-100°C). A similar tendency has also been observed for C. sinensis black and green teas, where infusion with greater antioxidant capacity was obtained at longer brewing time and higher temperatures (Sharpe et al, 2016). This finding implies that more phytochemicals and polyphenol derivatives from the A. borneensis leaves are infused into the water due most probably to the existences of more openings and interstices on the leaves, increasing the diffusion rate at higher brewing temperature.…”
Section: Effect Of Brewing Timesupporting
confidence: 76%
“…Figure 3A shows that the total antioxidant capacity of A. borneensis leaves increases abruptly with brewing temperature (in the range of 10-100°C). A similar tendency has also been observed for C. sinensis black and green teas, where infusion with greater antioxidant capacity was obtained at longer brewing time and higher temperatures (Sharpe et al, 2016). This finding implies that more phytochemicals and polyphenol derivatives from the A. borneensis leaves are infused into the water due most probably to the existences of more openings and interstices on the leaves, increasing the diffusion rate at higher brewing temperature.…”
Section: Effect Of Brewing Timesupporting
confidence: 76%
“…We should note that the total antioxidant capacity of the infusions of the C. asiatica, A. borneensis, and A. occidentale leaves is abruptly increased either with higher brewing temperature or longer brewing time [23]. Similar tendency has also been observed for C. sinensis black and green teas [24]. However, in our previous study, we have demonstrated that more than 90% of the total antioxidant capacity was achieved at brewing temperature of 60°C, for the first 3 min infusion time [23].…”
Section: Total Antioxidant Capacitysupporting
confidence: 69%
“…An increase in TPC resulted in the increase of DPPH radical scavenging in tea infusions, a study suggested higher water temperature and shorter steeping time as the best combination for improving the herbal teas beneficial health effects in terms of antioxidant properties (7). The antioxidant activity of green tea Liptón ® obtained in this study was compared with the study of another reported author who determined the activity of 24 commercial samples, where the brand Lipton ® reported 1000 μmol trolox eq/g per sample (23), similar to the results obtained by hot extraction (95.25 ± 0.24 mg trolox eq/g per sample). Catechin polyphenols are believed to be the most important active component in green tea.…”
Section: Discussionmentioning
confidence: 79%